1983
DOI: 10.1073/pnas.80.11.3504
|View full text |Cite
|
Sign up to set email alerts
|

Action of luteinizing hormone-releasing hormone: involvement of novel arachidonic acid metabolites.

Abstract: Anterior pituitary cells were incubated in the presence of luteinizing hormone-releasing hormone and one of three inhibitors of arachidonic acid metabolism: indomethacin, an inhibitor of the cyclooxygenase system; nordihydroguaiaretic acid, an antioxidant that inhibits lipoxygenase; and icosatetraynoic acid, an acetylenic analogue of arachidonic acid that blocks all known pathways of arachidonic acid metabolism. Indomethacin was ineffective in blocking luteinizing hormone-releasing hormone-stimulated luteinizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1
1

Year Published

1984
1984
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(57 citation statements)
references
References 21 publications
4
51
1
1
Order By: Relevance
“…the evidence that prostaglandins are the mediators of some of the effects of ethanol on the brain (34,35), increase in a pathway for the elimination of prostaglandins may influence the sensitivity of the brain to ethanol. Another pathway that could be influenced by an increase in the level of members of the P450 4A family in the brain is the release of peptides by dopamine (36). This release is thought to be mediated by epoxides of arachidonic acid that are formed through the action of P450.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…the evidence that prostaglandins are the mediators of some of the effects of ethanol on the brain (34,35), increase in a pathway for the elimination of prostaglandins may influence the sensitivity of the brain to ethanol. Another pathway that could be influenced by an increase in the level of members of the P450 4A family in the brain is the release of peptides by dopamine (36). This release is thought to be mediated by epoxides of arachidonic acid that are formed through the action of P450.…”
Section: Figmentioning
confidence: 99%
“…The role of P450 2C7 has not been investigated nor is there any information on the levels of retinoic acid in the brain after ethanol consumption. Another catalytic activity of some members ofthe P450 2C family that may be relevant in the brain is their arachidonic acid epoxygenase activity (42), which suggests a role in intracellular signaling (36).…”
Section: Figmentioning
confidence: 99%
“…It may be the major one in the proximal tubule as this area is deficient in cyclooxygenase and lipoxygenase (12)(13)(14). Interest-ingly, 5,6-EET increased [Ca2+]i in pituitary and parotid cells (15,16) and was implicated to mediate secretory responses (17)(18)(19)(20)(21). The mechanism whereby 5,6-EET increases [Ca2i] has not been investigated; other eicosanoids, such as PGF2,, PGE2, 5-hydroxyeicosatetraenoic acid (5-HETE), and leukotriene B4, are known to induce rises in [Ca2+i primarily from intracellular stores through IP3-dependent mechanisms and, to a lesser extent, through influx of extracellular Ca (22)(23)(24)(25)(26) …”
Section: Introductionmentioning
confidence: 99%
“…In anterior pituitary cells, recent studies have suggested that LHRH-stimulated LH release may be associated with the production of oxidized arachidonic acid metabolites [2,13,27]. One or more of the epoxygenated and/or lipoxygenated metabolites of arachidonic acid might be a component of the cascade of reactions initiated by LHRH that ultimately results in secretion of LH.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in inositol lipid metabolism has been observed within minutes following the exposure of anterior pituitary cells [2,3] or ovarian cells [4- Therefore, the present study was designed to determine whether arachidonic acid release in granulosa cells could be affected by a calcium ionophore, A23187, which alters the intracellular concentrations of Ca*+, as well as by a known activator of protein kinase C, TPA.…”
Section: Introductionmentioning
confidence: 99%